Rancang Bangun Sistem Penjualan Bunga Di Lembur Kuring Mini Garden - Ahmad Zuhdi; Ryan Aji Wijaya (LPPM Universitas Muhammadiyah Kotabumi, 2025)
This study aims to develop a desktop-based sales information system to address the limitations of manual data recording at Lembur Kuring Mini Garden, a small business specializing in flower seedlings. Rapid advancements in information technology and the need for accurate, structured, and efficient data processing highlight the importance of computerized systems in supporting business operations. Manual processes such as recording customer data, stock inventory, and sales transactions often lead to errors, data duplication, and delays in decision-making. To overcome these issues, the system was developed using the Software Development Life Cycle (SDLC), which includes planning, analysis, design, implementation, and testing. The application was built using Visual Studio 2012 with C# and SQL Server as the database management system, while Crystal Reports was utilized for generating sales and inventory reports. Data collection was conducted through interviews to obtain system requirements directly from the business owner. The implemented system consists of modules for managing customer data, flower stock, and sales transactions, each equipped with essential functions including add, edit, delete, search, and report generation. Black Box Testing was employed to evaluate system functionality, focusing on input validation, process accuracy, interface responsiveness, and output correctness, all of which showed successful results. The findings indicate that the developed system effectively replaces the previous manual process, improves operational efficiency, reduces recording errors, and provides more organized and reliable information to support decision-making. Overall, the system demonstrates its feasibility and relevance for small businesses that require structured and efficient sales and inventory management.